Acceptance and commitment therapy reduces psychological distress in patients with cancer: a systematic review and meta-analysis of randomized controlled trials - Jiang, Xing; Sun, Jian; Song, Ruiwen; Wang, Yue; Li, Jinglian; Shi, Rongwei (Frontiers in Psychology, 2024)
Objective This study aimed to systematically review and meta-analyze the clinical efficacy of acceptance and commitment therapy (ACT) in patients with cancer and psychological distress. Methods Randomized controlled trials (RCTs) from seven English electronic databases were systematically investigated from inception to 3 October 2023. A total of 16 RCTs from 6 countries with 711 participants were included in this study. Estimated pooled effect sizes (ESs) were calculated via inverse-variance random-effects or fixed-effects (I2 ≤ 50%) model and presented by standardized mean difference (SMD). Subgroup analyses were performed to reduce confounding factors and heterogeneity, and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was used to evaluate the quality of the pooled ESs. Results The pooled ESs revealed that statistically significant improvements in anxiety [postintervention SMD = −0.41 (95% confidence interval (CI), −0.71, −0.11); p = 0.008; I2 = 65%; follow-up SMD = −0.37 (95% CI, −0.66, −0.08); p = 0.01; I2 = 29%], depression [postintervention SMD = −0.45 (95% CI, −0.63, −0.27); p < 0.001; I2 = 49%; follow-up SMD = −0.52 (95% CI, −0.77, −0.28); p < 0.001; I2 = 0%], and psychological flexibility [postintervention SMD = −0.81 (95% CI, −1.50, −0.11); p = 0.02; I2 = 84%; follow-up SMD = −0.71 (95% CI, −1.12, −0.31); p = 0.0006; I2 = 38%] in ACT-treated participants were observed compared to patients treated with control conditions. However, other outcomes, such as physical symptom alleviation, were not significantly associated. Conclusion The findings of this systematic review and meta-analysis suggest that ACT is associated with improvements in anxiety, depression, and psychological flexibility in patients with cancer. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022320515.